Multi-objective Temporal Coordination of A Multi-Energy Microgrid with Demand Response - Zeng, Kaiwen; Wang, Haizhu; Liu, Jianing; Lin, Bin; Du, Bin; Hu, Chunchao (2020 IEEE 4th Conference on Energy Internet and Energy System Integration (EI2), 2020)
Currently, the demand response scheme is more and more popular with the widespread installation of the smart meters. Accordingly, the multi-objective optimal coordination of a multi-energy microgrid (MEMG) is investigated considering the multi-energy DR schemes. The operation objective is minimizing the net operating cost and gas emissions simultaneously under all the system operation constraints. As for the multiple demand response scheme, for electricity, the price-based DR (PBDR) is used; for the thermal (heat or cooling) energy, as the thermal energy system has higher inertia, then it can be used as the demand response scheme. To solve the multi-objective problem, the weighted sum method is used given the preference from the decision makers. Besides, for high solution quality, the original nonlinear operation model is linearized as a mixed-integer linear programming (MILP) one. Then it is efficiently solved by commercial solvers like Cplex and Gurobi. Finally, the validity of the proposed method is verified by a case study.